PERANCANGAN SISTEM PENGEREMAN DENGAN TEKNOLOGI MEDAN ELEKTROMAGNETIK PADA KENDARAAN - Abdul Basid; Arief Wisaksono (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
The braking system is one of the main components in a vehicle that plays an important role in driving safety. This research aims to design and develop an electromagnetic field-based brake system as an alternative to conventional brake systems. The system utilises the magnetic field generated by the solenoid to create braking force through the principle of electromagnetic induction. Simulation results show that the system is able to generate optimal braking force with faster response and higher energy efficiency. Prototypes tested on small-scale vehicles show improved braking performance with reduced braking distance compared to conventional brake systems. In addition, the system successfully reduced mechanical component wear and demonstrated good reliability under various conditions, including wet road surfaces. However, the research also found challenges in the form of relatively high energy consumption and the need for more heat-resistant conductive materials. In conclusion, electromagnetic brake systems have great potential to improve the safety, efficiency and sustainability of transport in the future. Recommendations for further research include optimising energy consumption, developing new materials, and testing on commercial-scale vehicles to ensure feasibility of implementationKeywords: Electromagnetic, Braking, Vehicle, Magnetic Field, Conventional Braking